Understanding Parents' Perceptions of School-Based BMI Screening and BMI Report Cards Using Perceptual Mapping: Implications for School Nurses. (April 2020) - Ruggieri, Dominique G.; Bass, Sarah Bauerle; Alhajji, Mohammed; Gordon, Thomas F.
Half of U.S. states measure students' body mass index (BMI), with many communicating that information to parents through a "BMI report card" or notification letter. School nurses are usually responsible for implementing these programs and communicating results to parents. The purpose of this study was to understand parents' perceptions of BMI screening programs to help inform school nurses about messages that are most helpful to use in report cards to motivate parents to follow-up with a health-care provider or to make behavioral changes for their child. Using a cluster analysis and perceptual mapping methods, a commercial marketing technique that creates three-dimensional graphic maps, we identified four unique clusters of parents based on their core attitudes and beliefs related to BMI screenings and report cards. Based on vector modeling techniques, key message strategies were developed that can be used by school nurses to enhance parent response to a BMI report card.